No association between binge eating disorder and severity of non‐alcoholic fatty liver disease in severely obese patients. Issue 3 (1st March 2020) - Canivet, Clémence M; Perney, Pascal; Cherick, Faredj; Orlowski, Magalie; Patouraux, Stéphanie; Bailly‐Maitre, Béatrice; Tran, Albert; Iannelli, Antonio; Gual, Philippe; Anty, Rodolphe
Abstract : Background and Aim: The main aim of this study was to evaluate if the binge eating disorders (BEDs) related to obesity were associated with the severity of non‐alcoholic fatty liver disease (NAFLD). Methods: Severely obese patients who had been referred for bariatric surgery were included in this study at the Nice University Hospital. All patients underwent a liver biopsy at the time of surgery. Between 2008 and 2015, 388 patients had an assessable Bulimia Test (BULIT) self‐questionnaire at the time of surgery. A subgroup ( n = 183), between 2011 and 2015, also responded to a Beck Depression Inventory, Hospital Anxiety and Depression Scale, and a Fatigue Impact Scale autoquestionnaire. A control group of 29 healthy people matched by age and gender was included. Results: Among the 388 obese patients (median age 40 years, body mass index 41.7 kg/m 2, 81% women), 14 patients had a "probable diagnosis" of BED, and 47 patients had a "high risk" of developing a BED according to the BULIT. Obese patients had significantly more severe BED, depression, anxiety, and fatigue compared to controls. Steatosis, non‐alcoholic steatohepatitis, or fibrosis was not associated with BED. Similarly, the severity of NAFLD was not associated with depression, anxiety, or fatigue. Conclusions: Severely obese patients had more severe BED, depression, anxiety, and fatigue than lean subjects independent of the severity of NAFLD. Abstract : Non‐alcoholic fatty liver disease, the emerging liver disease of the 21st century, is related to obesity. However, binge eating disorders, and also frequently associated psychiatric disorders (depression, anxiety, and fatigue), are not associated with the severity of liver pathology in severely obese patients.